Treating addiction : a guide for professionals - Miller, William R.; Forcehimes, Alyssa; Zweben, Allen , 1940- (New York : Theguilford Press, 2011)
"An indispensable practitioner reference and text, this engaging book focuses on how to provide effective help to clients with substance use disorders. The authors, leading authorities on addiction treatment, present a state-of-the-art framework for assessment and treatment. They describe and illustrate evidence-based treatment methods, including cognitive-behavioral, 12-step, motivational, pharmacological, and family approaches. Also addressed are such crucial clinical issues as resistance, maintenance of change, treating co-occurring disorders, and spirituality. Reproducible clinical tools can be photocopied from the book or downloaded and printed in a convenient 8 1/2" x 11" size. Of special utility, the companion Web page features more than 25 additional widely used, ready-to-download assessment tools, assembled in one place for the first time, together with the authors' guidance for using them throughout the process of treatment"--Provided by publisher.
1. An invitation to addiction treatment -- 2. A context for addiction treatment -- 3. A menu of evidence-based options for addiction treatment -- 4. Issues that arise in addiction treatment
Machine generated contents note: PrefaceI. An Invitation to Addiction Treatment1. Why Treat Addiction?2. What Is Addiction?3. How Do Drugs Work?II. A Context for Addiction Treatment4. A Client-Centered Foundation5. Screening, Evaluation, and Diagnosis6. Detoxification and Health Care Needs7. Matching: Individualizing Treatment Plans8. Case ManagementIII. A Menu of Evidence-Based Options for Addiction Treatment9. Brief Interventions10. Enhancing Motivation for Change11. A Community Reinforcement Approach12. Strengthening Coping Skills13. Involving and Working with Family14. Mutual Help Groups15. Pharmacological Adjuncts IV. Issues That Arise in Addiction Treatment16. Responding to Resistance17. Enhancing Adherence18. Treating Co-Occurring Disorders19. Promoting Maintenance20. Working with Groups21. Addressing the Spiritual Side 22. Professional Ethics23. Promoting PreventionPostscript: Looking Forward, A. Thomas McLella
Includes bibliographical references (p 391-448) and index
Keywords: Drug abus -- Treatment; Substance abus -- Treatment